PROSES FINALISASI PERBATASAN HINDIA-BELANDA - NORTH BORNEO (SABAH): SEBUAH CATATAN ATAS MARJINALISASI AKHIR KESULTANAN SULU DI PESISIR TIMUR-LAUT KALIMANTAN - Lumenta, Dave (JURNAL ILMU BUDAYA, 2014)
This article is aimed to reveal the process through which the role of the Sultanate of Sulu over the northeast coast of Borneo was ended. This process is significant to understand why the claim of the Sultanate of Sulu over Sabah no longer included Tidung and Bulungan areas even though in the past they had. The most controversial claim by the Dutch was that the Sultan of Bulungan had signed a treaty with them in 1850 which mentioned that the territory of Bulungan inculded Batu Tinagat, Sungai Tawau, Nunukan Island, Sebatik Island, and Tarakan Island. Using historical sources such as the Resolution of the Governor General of the Netherlands Indies (1846), Memorandum of the North Borneo Cession (1882-1884) and others, this article is an attempt to reveal the process through which the borders of the Sultanate of Sulu on the Northcoast of Borneo/ Kalimantan in ciolonial times was negotiated.Keywords: Sabah, Sulu Sultanate, borders, colonia, history